SOSIALISASI MANFAAT MAKAN IKAN SEBAGAI UPAYA PENCEGAHAN STUNTING DI POSYANDU TULIP DESA MAKRAMPAI KECAMATAN TEBAS: Socialization of the Benefits of Eating Fish as an Effort to Prevent Stunting at Tulip Posyandu, Makrampai Village, Tebas District - Anggi; Sakira Marantika; Irfansyah; Idris; Nurazizah; Wariah; Erdika Epril Saputra; Galih Pratama (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Consuming fish is something that must be done routinely to stay physically and spiritually healthy. In our lives, we also need to pay attention to a healthy lifestyle to avoid various kinds of diseases that attack our bodies and the benefits of consuming this fish can also educate the brain for mothers and children because, Consuming fish plays a role in improving children's nutrition, acting as an antioxidant, educating children and reducing the risk of heart disease and maintaining the health of the mother and fetus, and also consuming fish can help the child's body develop, such as: Protein helps stimulate the growth of toddler brain cells, Omega 3 can improve brain function and mood in children, especially in learning, memory and brain development, Calcium functions for bone growth and development of the nervous system and muscle function in children's bodies, Vitamin A can be useful in preventing blindness and improving vision in children, Socialization activities it on November 14, 2022, this socialization activity can later increase knowledge about consuming fish and the system used by distributing brochures to mothers, and also providing detailed explanations regarding the themes raised which were carried out in Mak Rampai Village, Tebas District